Mursilis’ Northwestern Campaigns — Additional Fragments of His Comprehensive Annals - Houwink ten Cate, Philo H. J.
I = KBo VIII 34 + 2301/c; II = 539/b; III = 2768/c I; IV = KBo XIV 20 I + XXXIV 33 and 34; V = 2764/c II; VI = KBo VII 17 + 2807/c I; VII = XXXIV 36; VIII = XIV 18 =2 BoTU 67 duplicated and continued by 154/c; IX = 1561/c; X = XIV 19; XI = KBo XIV 20 II; XII = KBo XIV 19 II; XIII = KBo XIV 19 III; XIV = KBo VII 17 + 2807/c IV; XV = XIV 25 = 2BoTU 66.